Benarkah Faktor Gender Berperan dalam Pengungkapan Kekerasan Seksual Anak? Studi Meta Analisis - - Suryani (Jurnal Psikologi, 2009)
This article provides a meta analitic review of the role of gender and disclosure of child sexual abuse. The subject in this studies is victims of child sexual abuse with restropective studies. Gender factors can be role in disclosure of child sexual abuse when the findings aggregated across studies. It was found that after sampling erros correction was ř = 0.127. These finding indicates that gender have roles in disclosure of child sexual abuse.There are differents between males and females to disclosure of child sexual abuse, This finding supports that females may be less likely than males to disclosure.